Perancangan Alih Fungsi Kontainer Menjadi Modul Ruang Komersial “Fasilitas Makan dan Minum” - Lie, Devi Sugiarto; Yusita Kusumarini; Meirina Kuncahyowati (Intra, 2019)
Micro, Small, Medium Enterprises (MSME) have a huge contribution in economic improvement. This fact needs to be supported with real actions from many parties to develop the existing MSME. One thing that we can do to help them is by giving them alternative business space. Using unused containers is one of the alternatives that can be used as business space. Surabaya is a harbor city that have a lot of unused containers. Therefore, unused containers are easily obtained and by using it, we can reduce the piled-up containers. Container itself have some benefits, it can be easily moved and has a strong construction and material that can be re-function to become a business space. The method that is used to realize it, is “design thinking” which includes understand, observe, point of view, ideate, prototype, test and implementation. We expect that the design of commercial space modules for food and beverages facilities can be an alternative business space for MSMEs or prospective entrepreneurs who want to start a new business. This commercial space module, especially in food and beverages’ area, give some benefits for the user, it help the brand to be easily known, more reachable, and increase their profit.